Criminal Justice in Northern and Remote Communities: Redressing the Substantive Inadequacies in Achieving Long-Term Justice for Indigenous Youth - Aho, Alison (Université d'Ottawa / University of Ottawa, 2019)
In spite of legislative, judicial, and governmental initiatives, Indigenous youth continue to face over-representation in the Canadian criminal justice system. While the Government of Canada appears to be closer than ever to accepting wide scale self-governance of Indigenous peoples, there are a number of obstacles within the proposed solutions that will continue to prevent Indigenous youth from achieving sentencing equity. This thesis asks the question, to what extent can the Youth Criminal Justice Act and supporting regulations be reformed in order to effectively “rehabilitate and reintegrate” Indigenous youth and serve the Government of Canada mandate of “reconciliation;” or, considering the colonialist underpinning of Canadian legislation, to what extent do Indigenous youth require alternative solutions to establish equitable justice? In answering this question, this thesis engages the theoretical framework of Critical Race Theory to examine existing legislation, jurisprudence, programs, and institutions geared towards creating sentencing equity for Indigenous youth in Canada, ultimately proposing recommendations for a more fair criminal justice system.
Keywords: Criminal law; Youth; Justice; Law; Indigenous; Sentencing